Address by Alhaji Shehu Shagari, President of the Federal republic of Nigeria and commander-in-chief of the armed forces on : the occasion of the presentation of the 1983 budget proposals to the national assembly (Nigeria : Federal republic of Nigeria, 1982)
This handbook is a budget proposal presented by the President of the Federal Republic of Nigeria in 1982. The presidential speech contains proposed budget allocation to various ministries and agencies working under the jurisdiction of the Federal Republic of Nigeria
asm; 15/04/19
Loans
Keywords: Budget; Nigeria